Evidence for Dechlorination of Polychlorinated Biphenyls and Polychlorinated Dibenzo-p-Dioxins and -Furans in Wastewater Collection Systems in the New York Metropolitan Area - Rodenburg, Lisa A; Du, Songyan; Lui, Hui; Guo, Jia; Oseagulu, Nicole; Fennell, Donna E (Environmental science & technology, 2012)
Polychlorinated biphenyls (PCBs) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) are persistent organic pollutants targeted by the Stockholm Convention. Both contain aromatic chlorines and are subject to microbial dechlorination. Dechlorination of PCBs in sewers in the Delaware River basin was recently reported. In this work, two data sets on concentrations of PCBs and PCBs+PCDD/Fs in wastewater treatment plant influents and effluents were analyzed to look for evidence that these compounds undergo dechlorination in the sewers of the New York/New Jersey Harbor area. The two data sets come from the Contamination Assessment and Reduction Project (CARP) and were analyzed via Positive Matrix Factorization (PMF). Analysis of the data set containing only PCB concentrations suggests that PCBs are dechlorinated in the sewers of the NY/NJ Harbor via the same pathways observed in the sewers of the Delaware River basin and that advanced dechlorination of PCB mixtures is more likely to occur in combined sewers vs separate sanitary sewers. When the combined data set of PCBs+PCDD/Fs was analyzed, the factor containing PCB dechlorination products also contained high proportions of 1,2,3,4,6,7,8-heptachlorodibenzo-p-dioxin (HpCDD), a known product of the dechlorination of octachlorodibenzo-p-dioxin (OCDD), and other known dechlorination products of PCDD/Fs. Despite being the most abundant PCDD/F congener in all of the samples in the database, OCDD was a minor component in the dechlorination factor. This provides the first evidence that PCDD/Fs may be dechlorinated in sewers.